2015
DOI: 10.1002/bies.201400198
|View full text |Cite
|
Sign up to set email alerts
|

Adult neural stem cells: Long‐term self‐renewal, replenishment by the immune system, or both?

Abstract: The current model of adult neurogenesis in mammals suggests that adult-born neurons are generated by stem cells that undergo long-term self-renewal, and that a lifetime supply of stem cells resides in the brain. In contrast, it has recently been demonstrated that adult-born neurons in crayfish are generated by precursors originating in the immune system. This is particularly interesting because studies done many years ago suggest that a similar mechanism might exist in rodents and humans, with bone marrow prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 92 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…These parallels between the life‐long neurogenic mechanisms of two taxa as phylogenetically distant as crayfish and mammals may serve as another illustration of how evolution independently generates similar solutions when faced with similar challenges. Seen from this perspective, the recently discovered novel mode of NP pool replenishment via integration and neural differentiation of hemocytes in the crayfish DPS (Benton et al, ) may well represent a more ubiquitous pathway than originally appreciated and thus inform the future direction of studies on mammalian systems (see Beltz et al, ; Beltz, Brenneis, & Benton, for further discussion).…”
Section: Discussionmentioning
confidence: 99%
“…These parallels between the life‐long neurogenic mechanisms of two taxa as phylogenetically distant as crayfish and mammals may serve as another illustration of how evolution independently generates similar solutions when faced with similar challenges. Seen from this perspective, the recently discovered novel mode of NP pool replenishment via integration and neural differentiation of hemocytes in the crayfish DPS (Benton et al, ) may well represent a more ubiquitous pathway than originally appreciated and thus inform the future direction of studies on mammalian systems (see Beltz et al, ; Beltz, Brenneis, & Benton, for further discussion).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support this hypothesis is shown in Figure 3, where in situ hybridization for CHF mRNA clearly shows cells with and without CHF expression (a marker for SGCs) (Figure 3). Recent studies have also shown a link between the immune system and adult neurogenesis in crayfish; therefore, cells within the APC and/or HPT likely give rise to neuronal precursors (Beltz et al, 2015(Beltz et al, , 2011Benton et al, 2014). However, to obtain a clear picture of how commitment and differentiation are regulated in this tissue, it is absolutely necessary to identify additional markers for the different stages of development into different mature hemocyte types, as illustrated in Figure 3.…”
Section: Hemocyte Lineages and Releasementioning
confidence: 99%
“…Pulse‐chase experiments with proliferation markers such as BrdU in clawed lobsters, spiny lobsters and crayfish have provided strong evidence that these newly born neurons within the proliferation zones survive and are integrated into the existing circuitry of the central olfactory pathway (Harzsch et al, ; Schmidt, ; Sullivan and Beltz, ; Sullivan et al, ; b; Kim et al, ). The rate of mitosis as well as survival and differentiation of the newly born cells within the crustacean deutocerebrum are modulated, for example, by the neuromodulator serotonin, rearing conditions (“impoverished versus enriched environment”), circadian and seasonal effects, social interactions and locomotory activity (reviews Sandeman et al, ; Benton et al, ; Schmidt, ; Sandeman et al, ; Beltz et al, ).…”
Section: Introductionmentioning
confidence: 99%